Government Spending Pattern and Macroeconomic Stability in Nigeria: A Vector Autoregressive (VAR) Model - Amuka, Joseph I.; Ezeoke, Miracle O.; Asogwa, Fredrick O. (International Journal of Economics and Financial Issues, 2016)
Macroeconomic stability has not kept pace with the pattern of Public sector spending in majority of the developing countries. Unfortunately, past studies have mainly focused on the consequences of aggregate government spending on macroeconomic variables, or at most disaggregated government spending into capital and recurrent. In order to use government spending to effectively bring macroeconomic stability in developing countries, government spending must be decomposed according to sectors. Only very few studies have done this. We made effort to find out the components of government spending that cause macroeconomic instability in Nigeria, using Vector Autoregressive (VAR) Model. Result reveals government capital expenditure on economic services is the major cause of inflation in Nigeria. Impulse response function shows inflation will respond very sharp and positively to any shock in government capital spending in economic sector and social and community services. Therefore, if government must pursue economic stability through inflation control, she must re-examine her investment in those sectors. Keywords: Government, Spending, Pattern, Macroeconomic, Stability JEL Classifications: H5, E6